2020
DOI: 10.9734/arrb/2020/v35i830262
|View full text |Cite
|
Sign up to set email alerts
|

Production of Peanut Milk and Its Functional, Physiochemical, Nutritional and Sensory Characteristics

Abstract: This study was aimed to investigate the functional properties of peanut seeds, and physicochemical, nutritional and sensory analysis of processed peanut milk. Standard methods were used in this research to determine the functional properties and proximate composition, while minerals were determined by a flame photometer and colorimeter. Firstly, the functional proprieties of the whole and defatted kernel of peanut seeds were studied, and the best results were found in the defatted sample. Peanut milk samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…that the rising water ratio leads to a decrease significantly in carbohydrate content in samples (p<0.01). Similarly, the result was found in the study which the carbohydrate content of peanut milk ranged from 3.3% to 7.5% [26]. Another studies reported similar results that increasing of water ratio can decrease the carbohydrate content [30].…”
Section: Protein Contentsupporting
confidence: 76%
“…that the rising water ratio leads to a decrease significantly in carbohydrate content in samples (p<0.01). Similarly, the result was found in the study which the carbohydrate content of peanut milk ranged from 3.3% to 7.5% [26]. Another studies reported similar results that increasing of water ratio can decrease the carbohydrate content [30].…”
Section: Protein Contentsupporting
confidence: 76%